2024
DOI: 10.3390/curroncol31040133
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of Performance Status during Palliative Radiotherapy Suggests a Significant Short Survival Duration: Indicating the Necessities for Considering Radiotherapy Discontinuation

Hitoshi Maemoto,
Kazuaki Kushi,
Isoko Owan
et al.

Abstract: Discontinuation of palliative radiotherapy due to a patient’s declining general condition poses a clinical dilemma for palliative care physicians. This study aimed to investigate the survival duration of patients whose performance status (PS) deteriorated during palliative radiotherapy and inform decisions regarding early treatment discontinuation. We retrospectively analyzed data from patients referred from our institute’s palliative care department who underwent ≥10 fractions of palliative radiotherapy betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Interestingly, in a very recent trial from Maemoto et al, the deterioration of ECOG PS during radiotherapy treatment was directly correlated with survival, suggesting that, in these cases, the discontinuation of treatment should be considered [ 30 ]. None of the patients in our study showed signs of symptoms worsening; on the contrary, a significant proportion experienced improvement in pain symptoms even before the completion of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a very recent trial from Maemoto et al, the deterioration of ECOG PS during radiotherapy treatment was directly correlated with survival, suggesting that, in these cases, the discontinuation of treatment should be considered [ 30 ]. None of the patients in our study showed signs of symptoms worsening; on the contrary, a significant proportion experienced improvement in pain symptoms even before the completion of treatment.…”
Section: Discussionmentioning
confidence: 99%